## ddx cosx

### To find the derivative of cos(x) with respect to x, we can use the chain rule

To find the derivative of cos(x) with respect to x, we can use the chain rule.

The chain rule states that if we have a composite function f(g(x)), then the derivative of f(g(x)) with respect to x is given by f'(g(x)) * g'(x).

In this case, f(u) = cos(u) and g(x) = x. So, we can rewrite cos(x) as f(g(x)) = f(u) = cos(u), with u = x.

Now, let’s find the derivatives of f(u) and g(x):

The derivative of f(u) = cos(u) with respect to u is given by f'(u) = -sin(u).

The derivative of g(x) = x with respect to x is simply g'(x) = 1.

Now, using the chain rule:

ddx (cos(x)) = f'(g(x)) * g'(x).

Substituting the derivatives we found:

ddx (cos(x)) = -sin(g(x)) * 1.

Since g(x) = x, we can rewrite the equation as:

ddx (cos(x)) = -sin(x).

Therefore, the derivative of cos(x) with respect to x is -sin(x).

## More Answers:

Finding the Angle Whose Sine is -1: Understanding the Reference Angle and Principal AngleFinding the Value of cos^-1(1): Understanding the Inverse Cosine Function and its Angle Representation

Understanding the Chain Rule: Finding the Derivative of sin(x)